A Review of the Role of Understory Technologies for Carbon Neutrality - Zhang Xue (International Journal of Engineering and Management Research, 2023)
Carbon emissions are considered the main cause of global warming. The mainstream scientific community has reached a consensus on this, which stimulates international political responses and promotes research on carbon emissions and their reduction in the economics community. At the 75th session of the UN General Assembly, President Xi Jinping solemnly promised that China will strive to peak its carbon emissions by 2030 and achieve carbon neutrality by 2060. Carbon emission reduction has received more attention. At the same time, the under-forest economy is regarded as a new growth point for carbon emission reduction. This paper focuses on reviewing the history of carbon emissions, the development of carbon emission reduction in China, and the economic analysis of China's carbon emission reduction policies. China's carbon emission reduction policy has been implemented for more than ten years, especially the carbon trading pilot policy, which has been implemented for seven years. Are state efforts effective? What is the current state of the carbon emission reduction market? What is the role of understory economy in reducing carbon emissions? The article also answers the above points.